Midnight on the Moon. - Osborne, Mary Pope (New York : Random House, 1996)
Jack and Annie are whisked forty years forward in time and land at an international space station on the moon. There they don space suits and go exploring the lunar surface in search of the fourth object needed to free the enchantress Morgan le Fay from a powerful spell.
Illustrated in black-and-white. "A first stepping stone book."
All Juvenile
Keywords: Time travel--Fiction.; Magic--Fiction.; Science fiction; Moon--Fiction.